I CANNOT SMILE, DOCTOR. (29th November 2012) - Sokhi, D; Iqbal, A; Randall, M; Sarangmat, N
Abstract : A 24-year-old lady presented with first unilateral facial weakness and rapidly progressed over a few days to severe facial diplegia, with difficulty walking and sensory disturbance in her extremities. Examination revealed bilateral lower-motor facial nerve palsies with no opthalmolplegia, proximal limb girdle weakness with diminished reflexes causing impaired mobilisation, and glove-and-stocking sensory loss. Investigations for an acute polyneuropathy syndrome showed normal blood results, including for vasculitic and infective causes. Contrast MRI demonstrated enhancement of cranial nerves V, VII and VIII bilaterally, and of the cauda equina. CSF protein was elevated at 1.79 g/l. Neurophysiology showed a demyelinating process in keeping with Guillain-Barre syndrome (GBS). A 5-day course of intravenous immunoglobulin was given, with good treatment effect allowing independent mobilisation, but the facial palsies improved only marginally and were treated supportively. Nerve enhancement in either cranial nerves or spinal nerves on contrast MRI in GBS is well known, more so in children. The adult-case literature reports patients with either cranial or spinal nerve involvement in the clinical presentation, but changes in both sets of nerves on MRI, or vice versa. Our patient is unique for having both significant cranial and spinal involvement in both her clinical picture as well as her MRI.